2020
DOI: 10.25081/cb.2020.v11.6100
|View full text |Cite
|
Sign up to set email alerts
|

Stress breeding of neglected tetraploid primitive wheat (Triticum dicoccum, Triticum carthlicum and Triticum polonicum)

Abstract: Ancient wheats are progressively more considered as valuable resources for genes of interest especially in organic and health food markets which could be introduced into cultivated varieties. Better evaluation of primitive wheats that symbolize a valuable genetic resource may provide breeders with important sources for biotic and abiotic stress tolerance. Emmer wheat (Triticum turgidum subsp. dicoccum) is one of the most ancient of cultivated cereals, makes good bread, higher in fiber than common wheat, emmer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…An alternative approach would be to promote the cultivation of einkorn and emmer wheats in harsh environments, especially in developing countries, depending on the demand and climatic conditions [233][234][235]. Triticum dicoccon, T. polonicum, T. carthlicum, and T. turanicum are sources of useful alleles for improving abiotic and biotic stress tolerance in modern wheat cultivars [195,234,236,237].…”
Section: Improved Tolerance To Drought Heat and Salinitymentioning
confidence: 99%
“…An alternative approach would be to promote the cultivation of einkorn and emmer wheats in harsh environments, especially in developing countries, depending on the demand and climatic conditions [233][234][235]. Triticum dicoccon, T. polonicum, T. carthlicum, and T. turanicum are sources of useful alleles for improving abiotic and biotic stress tolerance in modern wheat cultivars [195,234,236,237].…”
Section: Improved Tolerance To Drought Heat and Salinitymentioning
confidence: 99%
“…Some authors reported that Polish wheat grain could contain up to 27% of protein [3]. The protein content in grain of the Polish wheat accession under investigation was much lower, but significantly higher than in the check durum wheat cultivar (Table 2).…”
Section: Resultsmentioning
confidence: 84%
“…pseudocompactum is closer to medium hard wheats according to Haraszi et al's classification [36,37]or to semi-hard wheat cultivars (7 points) according to the grain hardness scale [18] than to durum wheat. This explains the fact that despite being tetraploid wheat, T. polonicum is traditionally is used in bread-making industry [3] and evaluated as an ingredient in bread production [7].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al, 2022). Domesticated emmer wheat, the ancestor of bread wheat, is known to be one of the most ancient cultivated cereals and is characterized by qualities such as high fiber content, resistance to biotic and abiotic stresses and ability to grow in adverse environmental conditions (Lucas et al, 2017;Saleh, 2020). Despite the exciting potential of emmer wheat to contribute to wheat improvement (Mohammadi et al, 2021;Zaharieva et al, 2010;Zohary, 2013), the evolution from wild to domestic emmer forms and the differentiation of domestic emmer are still largely unexplored topics.…”
Section: Introductionmentioning
confidence: 99%